Titanium aminophosphates: synthesis, characterization and orange G dye degradation studies. Issue 129 (16th December 2015) - Rajini, Anumula; Nookaraju, Muralasetti; Chirra, Suman; Adepu, Ajay Kumar; Venkatathri, Narayanan
Abstract : A group of titanium aminophosphate catalysts are synthesized and characterized in detail, and their catalytic application towards orange G dye degradation is studied. Abstract : Titanium aminophosphates are prepared using titanium tetraisopropoxide, orthophosphoric acid and aliphatic amines. The synthesized TNPAP, TNOAP and TNDDAP titanium aminophosphates are characterized using various physicochemical techniques. The catalytic activity of TNPAP, TNOAP and TNDDAP is studied for the degradation of orange G dye. TNDDAP is found to be most effective catalyst. The optimum conditions required for efficient orange G degradation are found to be pH = 3.0, [H2 O2 ] = 1.0 × 10 −3 M, [OG] = 1.0 × 10 −4 M and a TNDDAP catalyst dosage of 150 mg. TNDDAP efficiently catalyzes the degradation of orange G dye with 97.3% degradation after 250 min. These catalysts exhibit good reusability over five successive cycles. They have potential to be used as economical catalysts for dye degradation for industrial waste waters.